Integration of Green Innovation and Utilization of Digital Technology to Achieve Sustainable Competitive Advantage for Haseda Herbal Products in Medan City: Integrasi Inovasi Hijau dan Pemanfaatan Teknologi Digital untuk Mewujudkan Keunggulan Bersaing Berkelanjutan Produk Herbal Haseda di Kota Medan - Kesuma Wijaya, Octaviona; Nasution, Lisa Elianti (PROCEEDING INTERNATIONAL BUSINESS AND ECONOMICS CONFERENCE (IBEC), 2025)
This study aims to analyze the role of green innovation and the use of digital technology in achieving sustainable competitive advantage for Haseda herbal products manufactured by PT. Amanah Berkah Kencana in Medan. Growing public awareness of healthy lifestyles and a preference for natural products presents both opportunities and challenges for the herbal industry, which must be able to compete in an increasingly competitive market. This study uses a quantitative approach by distributing questionnaires to 100 Haseda consumers in Medan City, selected through purposive sampling. The data were analyzed using SPSS with stages of validity testing, reliability testing, classical assumption testing, and multiple linear regression analysis. The results showed that green innovation (X1) and the use of digital technology (X2) had a positive and significant effect on sustainable competitive advantage (Y). The use of digital technology has a more dominant influence (β = 0.474; sig. = 0.000) than green innovation (β = 0.234; sig. = 0.010). Simultaneously, both variables are able to explain 40.3% of the variation in sustainable competitive advantage. These findings confirm that the integration of green innovation with effective digitalization strategies is key to strengthening image, expanding market reach, and ensuring the sustainability of herbal product competitiveness amid increasingly fierce competition.